(Z)-4-[4-(Dimethylamino)benzylidene]-3-methylisoxazol-5(4H)-one - Li-sha Liu; Qi-fa Wang; Qingfang Cheng; Jun-lei Zhang (Acta Crystallographica Section E, 2009)
The title compound, C13H14N2O2, an isoxazol-5-one derivative, was synthesized by a one-pot, three-component condensation reaction of methyl acetoacetate, hydroxylamine hydrochloride and 4-(dimethylamino)benzaldehyde. All the non-H atoms are co-planar [r.m.s deviation = 0.0039 Å], with a Z configuration about the C=C bond. The dihedral angle between the phenyl ring and the isoxazole ring is 2.58 (19)°.